Association of silent hypoglycemia with cardiac events in non-diabetic subjects with acute myocardial infarction undergoing primary percutaneous coronary interventions - Zhang, Jian-wei; Zhou, Yu-jie (BMC cardiovascular disorders, 2016)
Some studies have shown that hypoglycemic episodes in diabetic patients might be associated with increased cardiovascular events. It is not clear whether episodes of silent hypoglycemia had greater prognostic value on cardiac events compared with normoglycemia or hyperglycemia in non-diabetic patients, so the aim of this study was to investigate the association of silent hypoglycemia and cardiac events in non-diabetic patients with acute ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (p-PCI). We enrolled non-diabetic patients with STEMI who underwent p-PCI and whose clinical and laboratory data were collected. Interstitial glucose values were recorded using a continuous glucose monitoring system (CGMS), and Holter monitoring was recorded for 3 days in parallel. Cardiac ischemia and ventricular arrhythmia was evaluated. Based on the inclusion and exclusion criteria, we enrolled 164 STEMI patients undergoing p-PCI for final analysis. A total of 280 episodes of silent hypoglycemia (CGMS glucose <70 mg/dl) were recorded. Episodes of silent cardiac ischemia were recorded in 50 of 280 hypoglycemic episodes. The incidence of silent cardiac ischemia during hypoglycemia was significantly higher than the incidence during both hyperglycemia and normoglycemia(P < 0.01). Moreover, we found a significantly higher frequency of ventricular extrasystoles (VESs) or nonsustained ventricular tachycardias (NSVTs) in patients with silent hypoglycemia. The average number of events of silent cardiac ischemia was also significantly increased in the silent hypoglycemia group (0.91 ± 0.82 vs. 0.35 ± 0.54, P < 0.01) compared with either hyperglycemia or normoglycemia group. Hypoglycemia was frequent and most of the time asymptomatic in non-diabetic patients with STEMI undergoing p-PCI. Silent hypoglycemia was associated with silent cardiac ischemia. STEMI patients with silent hypoglycemia had a significantly higher frequency of VESs or NSVTs.